Pengaruh Massage Terhadap Peningkatan Panjang Badan Pada Bayi Berat Lahir Rendah - Wiwi Kustio Priliana; Barkah Wulandari (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2018)
Background The number of low birth weight babies (LBW) in Indonesia is still quite high. WHO notes Indonesia is ranked ninth in the world. In Indonesia the prevalence of LBW is 5-27%, while in Yogyakarta the LBW prevalence rate in 2015 is 9.4%